Photonics, Devices, and Systems VI 2015
DOI: 10.1117/12.2073252
|View full text |Cite
|
Sign up to set email alerts
|

Ag on carbon nanowalls mesostructures for SERS

Abstract: We have elaborated substrates for surface enhanced Raman scattering (SERS) based on carbon nanowalls (CNW) deposited with Ag nanoparticles and thin Ag films. For carbon nanowalls deposited with silver nanoparticles, the achieved analytical enhancement factor SERS was from 50 to 2500.Much higher analytical enhancement factor of SERS, up to 5×10 4 , was obtained for carbon nanowalls deposited with thin Ag film. In this case the SERS signal is determined by fractal structure of carbon nanowalls covered by Ag film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…CNWs can also be employed in fuel cells since Pt(Cu)st/CNW catalyst has low Pt content and high specific surface [19]. In the chemical and biological area, CNWs improve surface enhanced Raman scattering (SERS), which is a powerful surface analysis tool for chemical and biological single-molecule detection and molecular diagnosis [20,21]. It was reported that ultrasensitive SERS substrates can be fabricated by decorating silver nanoparticles on thin CNWs or coating CNWs with thin silver film [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CNWs can also be employed in fuel cells since Pt(Cu)st/CNW catalyst has low Pt content and high specific surface [19]. In the chemical and biological area, CNWs improve surface enhanced Raman scattering (SERS), which is a powerful surface analysis tool for chemical and biological single-molecule detection and molecular diagnosis [20,21]. It was reported that ultrasensitive SERS substrates can be fabricated by decorating silver nanoparticles on thin CNWs or coating CNWs with thin silver film [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In the chemical and biological area, CNWs improve surface enhanced Raman scattering (SERS), which is a powerful surface analysis tool for chemical and biological single-molecule detection and molecular diagnosis [20,21]. It was reported that ultrasensitive SERS substrates can be fabricated by decorating silver nanoparticles on thin CNWs or coating CNWs with thin silver film [20,21]. Seo et al [22] demonstrated that gold-and palladium-decorated honey-VG sheets offer reliable sensing performance for Au tagged antibodies as well as H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…CNW substrates already were also used for SERS measurements by a few groups. In work 15 SERS behavior of Ag nanoparticles and thin films on CNWs was studied. The work 15 studied SERS performance of electrochemically deposited Ag nanoparticles on CNWs.…”
Section: Introductionmentioning
confidence: 99%
“…In work 15 SERS behavior of Ag nanoparticles and thin films on CNWs was studied. The work 15 studied SERS performance of electrochemically deposited Ag nanoparticles on CNWs. In aforementioned works Ag shows excellent SERS activity but due to the chemical instability and tendency to degrade by exposure to air it is hardly suitabe for quantitative SERS studies.…”
Section: Introductionmentioning
confidence: 99%